Legal and ethical issues for health professions - McTeigue, Jeanne; Lee, W. Christopher (William Christopher) (Elsevier, 2015)
With all of the information you need to prepare yourself for legal and ethical situations in the healthcare setting, this title provides balanced coverage of the issues students and professionals face daily.